Making the microbiome public: Participatory experiments with DNA sequencing in domestic kitchens. Issue 3 (3rd March 2019) - Lorimer, Jamie; Hodgetts, Timothy; Grenyer, Richard; Greenhough, Beth; McLeod, Carmen; Dwyer, Andrew
Abstract : Recent rapid increases in the capability and affordability of DNA sequencing have enabled scientists to map the microbiome and to identify its associations with a range of health conditions. Concerns are growing that missing microbes might be behind the current rise in inflammatory disease. Microbial absence and dysbiosis have been linked to a range of hygiene practices, fuelling popular anxiety and confusion about being both too clean and the risk of superbugs. A growing number of microbiology projects allow some publics to engage with DNA sequencing, and enable DIY experiments in microbiome management. Advocates promote this as the democratisation of sequencing. This paper outlines a new methodology for making the microbiome public, and explores the potential of thinking with microbes for social science research. It reports on an interdisciplinary research project, in which a small number of households in Oxford designed and conducted repeated experiments on their kitchen microbiome. These experiments explored the composition of the microbiome and the effects of different hygiene practices. The analysis identifies two challenges of public microbiome research: the mismatch between a vernacular species ontology and the ecological understanding of the microbiome, and the difficulties posed by scientific uncertainty. The reported methodology was able to engage publics in the design and interpretation of experiments, and to work with the surprises generated by open research. Thinking with microbes as ecologies revealed the tensions between an antibiotic and a probiotic approach to domestic hygiene. Public microbiome research needs new metaphors and visualisation tools, and an awareness of the political economic and epistemic barriers that will configure the promised democratisation of sequencing. The conclusion calls for further interdisciplinary and participatory microbiome research to guide the emergence of this new technology. Abstract : This paper offers a new methodology for making the microbiome public. It examines how thinking with microbes offers new approaches to researching domestic hygiene practices. The paper presents a social science research agenda for shaping the emerging technology of high‐throughput sequencing.